CHANGES IN THE MICROCIRCULATORY BED OF THE LIVER DURING ALCOHOLIC HEPATITIS MODELING - Mykytenko, A.O.; Akimov, O.Ye.; Yeroshenko, G.A.; Shevchenko, O.M.; Neporada, K.S. (World of Medicine and Biology, 2023)
It is well known that chronic alcohol consumption leads to multiple organ damage and microcirculation disorders of organs and tissues. The aim of the work was to study the morphometric indicators of the microcirculatory bed of rat liver during alcoholic hepatitis modeling. The experiments were performed on 30 white, mature male Wistar rats, weighing 180–220 g. The animals were divided into 2 groups: I – control; group II– animals, on which we modeled alcoholic hepatitis according to Yu.M. Stepanov. (2017). The diameter of the sinusoidal capillaries around the central vein and the hepatic triad was increased at all time points compared to the control. The diameter of the lumen of the central vein of the hepatic lobe of rats increased on the 1st, 5th and 7th day of the experiment. The diameter of the lumen of the interlobular artery of rats was decreased during the studied periods, and the interlobular vein was increased. The diameter of the lumen of the arteriole increased on the 3rd day of the experiment, and the diameter of the lumen of the venule of the lobule of the rats decreased on the 1st day of the experiment. The microcirculatory channel of the liver of rats under the conditions of simulation of chronic alcoholic hepatitis in the first week demonstrates an increase in the exchange of metabolites between the central vein and the vein of the triad, which is accompanied by their expansion and threatens the development of venous hyperemia.
Keywords: chronic alcohol hepatitis; liver; microcirculatory channel; rats